Signal transduction and activation of transcription factor 3 (STAT3) mediates neonate hypoxic ischaemic brain injury. (7th June 2011) - Hristova, M; Thei, L; Gostelow, N; Peebles, D; Behrens, A; Akira, S; Raivich, G
Abstract : Hypoxia-ischaemia (HI) is a major cause of neonatal brain injury. Although a number of biochemical cascades have been implicated, the downstream targets, at the level of transcriptional regulation still remain unclear. The signal transduction and activator of transcription factor 3 (STAT3) is strongly upregulated following peripheral and central trauma and thus a possible candidate. In the current study, we investigated the regulation and functional role of STAT3 in the neonatal HI brain injury in the Rice-Vannucci model in postnatal day 7 mice, using 30 (mild) or 60 min (severe) exposure to 8% Oxygen and assessment of outcome based on size of infarct (Nissl), extent of cell death (TUNEL density) and microglial activation (alphaM&X levels). On immunohistochemical level, HI insult resulted in transient upregulation of phosphorylated STAT3 (Y705) in cortical, hippocampal and thalamic neurons, with a peak at 2–4 h after insult. Moreover, cell-type specific deletion of STAT3 in neurons using Synapsin:Cre in homozygous STAT3-flox mutant mice (n=5) resulted in a significant and strong reduction of tissue damage (−80%, p<5% t-test) in hippocampus, cortex, striatum and thalamus following the severe, 60 min insult, compared with their STAT3+ littermate controls (n=5). A more moderate effect was also observed in the subcortical white matter. We are currently exploring the results in the milder, 30 min HI, to obtain data on severity-specific sensitivity to STAT3 deletion. Since Y705-phosphorylation plays an important role in STAT3 function, the use of direct kinase inhibitors could serve as a candidate target for therapeutic intervention in neonatal brain damage.